Estética gótica: uma busca pela inserção dos adeptos da subcultura com a sociedade por meio do vestuário - Campos, Aline Fortes (2013)
This study presents a proposal for a clothing collection for public "goth/darkwave", whose aesthetics of the product intends to function as a means of unite the persons adept of this subculture with other social communities. Brings, through bibliographical survey, information on the emergence of the subculture throughout history, their classification into types and groups, aesthetic and symbolic values considered significant to the tribe, as well as presenting aspects regarding the gothic aesthetic influences in society and fashionable. It also presents a study of psychodynamic colors and their possibilities as sensory value in product development. Through field research, data is collected to help in identifying the interests of the consumer audience. Subsequently, these data are analyzed in order to verify which the most appropriate strategies for targeting merchandising of this research.